(untitled) (Pesquisa Odontológica Brasileira, 2003)
Cyanoacrylate has been used in medicine and dentistry for many years. It has been used as a postextraction dressing and retrograde filling material in endodontic surgery. The aim of this study was to evaluate the cytotoxic effects of Histoacryl and other two homologue ethyl cyanoacrylates, Super Bonder and Ultrabond, on cultured fibroblasts, using the Trypan blue dye exclusion assay. The cyanoacrylates were applied to round glass coverslips, which were placed in contact with NIH 3T3 cells. After 0, 6, 12 and 24 h (short-term assay; viability) and 1, 3, 5 and 7 days (long-term assay; survival), the cells were examined under phase light microscopy and counted. The data were compared by the Kruskal-Wallis test. In the short-term experiments, only the cultures of the Ultrabond group (GIV) presented significant smaller percentages of cell viability than the cultures of the other groups (GI: control; GII: Super Bonder; GIII: Histoacryl). Although the cultures of the Super Bonder group (GII) presented smaller percentages of cell viability than cultures of the other groups (GI, GIII, GIV) at the long-term assay, this group was the only experimental group presenting a continuous and progressive cell growth. Our results have shown an in vitro biocompatibility of Histoacryl and ethyl cyanoacrylate homologues. These cyanoacrylates could therefore be of importance for endodontic purposes.